IMPLEMENTASI KEBIJAKAN BANTUAN OPERASIONAL SEKOLAH ( BOS ) DI SDN TLOGOSARI WETAN 01 KECAMATAN PEDURUNGAN KOTA SEMARANG - Galih Wardana; Slamet Santoso; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2013)
Education is a planned effort in the development of self in order to realize the potential of a civilized society, morality, personality, intelligent and have a prosperous life skills (spiritual-knowledged based society). Which is currently able to improve the quality of education in Indonesia is through fund School Operational Assistance (BOS) allocated to schools at primary and secondary School Operational Assistance Program is a central government assistance to all students SD / MI and SMP / MTs underprivileged throughout Indonesia both public and private on reduction of fuel subsidy because it was feared that the increase in fuel prices and the global financial crisis caused a decline in purchasing power and will negatively impact the poor to get an education.The purpose of the research to find out and get a clear picture about the implementation of the BOS program on SDN Tlogosari Wetan 01 Sub Pedurungan, and used materials and used as an ingredient on the study of the implementation of the BOS program on SDN Tlogosari Wetan 01 Sub Pedurungan, Semarang.In this research used theory implementation of G Edward III which states "the successful implementation of depengaruhi by four variables: attitude, HR, Communications, Bureaucratic Structure"The method used in this research is descriptive qualitative research, where the research is more emphasis on the analysis and at the same time portraying the reality of the existing conditions, so the results of these studies are generating a lot of descriptive data in the form of words or in writing of the perpetrators were observed.Based on research conducted by the authors of the policy implementation of BOS in SDN Tlogosari Wetan 01 Semarang is fully effective, kaBerdasarkan research conducted by the authors of the policy implementation of BOS in SDN Tlogosari Wetan 01 Semarang is fully effective, because the indicators that lead to the achievement of BOS policy objectives set by the government much has been achieved, only the need for dissemination to relevant parties in relation to the BOS, and enhance the performance of human resources-related